Austenitic stainless steel sheet for photo-etching with excellent smoothness of material surface and etched surface, and its manufacturing method

JP7634127B1Active Publication Date: 2025-02-20NIPPON YAKIN IND KK +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024167402
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-20
Estimated Expiration
2044-09-26

Smart Images

  • Figure 0007634127000001_ABST
    Figure 0007634127000001_ABST
Patent Text Reader

Abstract

To provide a stainless steel capable of producing a high-quality paper-feed spur having excellent smoothness on both the plate surface and the etched surface and free from paper dust and scratches even when used for high-speed printing. [Solution] An austenitic stainless steel sheet for etching processing in which the contents of each of the elements are limited, by mass%, to: C: 0.010% or more, 0.10% or less, Si: 0.02% or more, 1.0% or less, Mn: 0.6% or more, 1.6% or less, Ni: 5.0% or more, 15.0% or less, Cr: 15.0% or more, 20.0% or less, Mo: 0.05% or more, 2.5% or less, W: 0.005% or more, 0.2% or less, Cu: 0.05% or more, 0.8% or less, N: 0.01% or more, 0.3% or less, B: 0.0001% or more, 0.0005% or less, and Sn: 0.002% or more, 0.02% or less, with the remainder consisting of Fe and unavoidable impurities, the ratio of the Cr concentration at the outermost surface to the Cr concentration in the base material being 0.90 or more, and the surface roughness (Ra) being 0.1 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an austenitic stainless steel sheet having excellent smoothness on the surface of the material and on the etched surface thereof and being used for photoetching processing, and a method for producing the same. [Background technology]

[0002] Photoetching is a process in which an oxidation-resistant resist film is formed on a metal surface using a photoresist method in the shape of the product, unnecessary parts are dissolved with an etching solution, and the resist film is then removed to obtain the product. Because this process is suitable for high-mix, low-volume production of parts with complex shapes, it is widely used in processing stainless steel thin sheets and foils.

[0003] Parts produced using this type of processing method include gimbal springs for hard disks, slits in rotary encoders, metal masks for vacuum deposition used as jigs in the production of ICs and LSIs, and paper feed spurs for inkjet printers, among many others.

[0004] For example, in the case of paper feed spurs, as the quality of printed images has improved, dedicated glossy paper has come to be used, and scratches on the printed paper caused by the spurs have become a problem. In addition, paper dust may be generated when the spur rubs against the printed paper surface. In such cases, the paper dust adheres to the peripheral surface of the spur, which is the part that contacts the printed paper surface, and to the surrounding area, and further, the paper dust absorbs ink and stains the printed paper surface. Recently, with the strong demand for high-speed printing, the problem of paper dust has become prominent again, and measures are required.

[0005] It is known that the generation of paper dust is strongly related to the quality of the spur tooth tips. The tooth tips are the left and right end parts of the spur shown in Figure 1(c) and Figure 2(c), and microscopically, the ends bite into the printed paper surface, so the parts that come into contact with the printed paper surface are both the plate surface (the bottom end surface in both figures) and the surface formed by etching (the inclined surface in both figures). Paper dust occurs when the plate surface that comes into contact with the printed paper surface, the etched surface, is not very smooth, and it is known that paper dust will not adhere even if it is generated if the surface roughness (Ra) is ≦0.10μm.

[0006] For example, in Patent Document 1, dislocations or martensite are introduced into the crystal grains to increase the etching rate within the crystal grains, and the etching rate within the crystal grains is made equal to that of the crystal grain boundaries, thereby obtaining a smooth etched surface. In addition, the smoothness of the material surface is obtained by a rolling process in which the material is cold-rolled at a rolling ratio of 20% to 80% using rolls with a surface roughness (Ra) of 0.2 μm or less during final rolling. However, even with the application of this technology, it is currently difficult to suppress the adhesion of paper powder.

[0007] Patent Document 2 also proposes a method of increasing the etching processing speed by having a segregated layer on the plate surface with a Ni concentration difference of 1.5 mass % or more, and by preferentially etching the parts with higher Ni concentration. However, this technology is a technology that improves the processing speed, and does not relate to the smoothness of the etched surface, which is related to the generation of paper dust.

[0008] Besides this, Patent Document 3 describes that the amount of C is set to 0.03 mass% or less in order to suppress the masking effect caused by corrosion products called smut, which are made of carbides, and the average crystal grain size is refined to 15 μm or less in order to increase the etching speed of the grain boundaries, and further, that 0.01 to 0.3 mass% of Nb is contained in order to suppress coarse carbides and crystal grain growth. However, the surface roughness that can be achieved by this technology is about 0.3 μm in Ra, and it is difficult to smooth it to Ra: 0.10 μm or less, which is the level at which paper powder does not accumulate. Therefore, it does not solve the above problems caused by the recent increase in speed.

[0009] Thus, at present, there is no suitable stainless steel for paper feed spurs that can keep up with the increasing printing speeds of today. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 4332670 [Patent Document 2] JP 2020-164905 A [Patent Document 3] JP 2003-3244 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention aims to provide a stainless steel sheet for etching which has excellent smoothness on both the sheet surface and the etched surface, in other words, which exhibits little change in shape between the sheet surface and the etched surface even after etching, and to provide a stainless steel which can be used to produce high-quality spurs which do not produce paper dust or scratches even when subjected to today's high-speed printing. [Means for solving the problem]

[0012] The inventors first conducted a detailed investigation into the cause of paper dust generation. The characteristics of paper dust generated by high-speed printing were that (1) the size of individual pieces of paper dust was smaller than before, and (2) the paper dust was observed to coalesce during high-speed printing. In addition, (3) it was found that the paper surface was somewhat rough at the contact area between the stainless steel surface and the etched surface. For this reason, it was decided to create an etched spur on one side of the plate and bring it into contact over a larger area in order to investigate the effect of (3) on paper dust generation.

[0013] Figure 1 shows a schematic cross-sectional view of the manufacturing process of a spur by etching. In Figure 1(a), resist 20 is applied to the entire back surface of the alloy plate 10 of the present invention, and resist 21 is applied to the front surface in the desired spur shape. In Figures 1(a)-(b), etching is performed in a normal manner, and dissolution progresses as shown by the arrows. The resists 20 and 21 are removed, and the spur shown in Figure 1(c) is obtained.

[0014] Figures 1(c) and 2(c) show schematic cross-sectional views of two types of spurs made by one-sided etching. When these spurs were observed, as shown in both figures, differences were observed in the sharpness of the tip just before the alloy plate was melted by etching and penetrated. They can be broadly classified into those with small shape changes as shown in Figure 1(c) (melting proceeds monotonically until the end) and those with large shape changes as shown in Figure 2(c) (melting changes midway). It was also found that certain lots showed large shape changes and others showed very small changes. This suggests the influence of the chemical composition of the alloy plate, and it was decided to conduct a more detailed investigation.

[0015] In addition, when a paper feed test was conducted with the manufactured spurs, it was confirmed that spurs that showed a large change in shape during etching generated a lot of paper dust, while spurs that showed a small change in shape generated little paper dust.

[0016] Therefore, to clarify the relationship between the change in shape and the chemical composition, the plate surface was analyzed in detail. As a result, it was found that the elemental concentration on the surface differed slightly for each lot. Since this was an analysis of elements contained in extremely small amounts, it is likely that there was some error, but Cr, Ni, Mo, W, Cu, Sn, and B were selected as candidates.

[0017] The effect of varying the concentration of each element in the alloy was examined, and it was found that when the Cr concentration on the plate surface was high and was the same as that of the base material, the change in shape was small, and conversely, when the Cr concentration on the plate surface was low, the change in shape was large. From this, it was presumed that the cause of the defect was that when etching was performed from one side of the plate, the part with a different Cr concentration was etched just before the penetration, which changed the properties of the spur tooth tip. In other words, as shown in the schematic cross-sectional view of Figure 2, when etching was performed in the same manner as in Figure 1 using an alloy plate 11 with a low surface Cr concentration, Cr-depleted layers 12 and 13 were formed, and it was thought that dissolution of the Cr-depleted layer 13 would proceed just before the etching penetration, as shown in Figure 2(b).

[0018] The candidate elements are thought to affect the Cr concentration on the surface, with Sn, Mo, W, and B having a particularly large effect on the occurrence of defects. Sn, Mo, and W tend to be good when concentrated on the sheet surface, while B was sometimes not detectable, and it was presumed that a better shape was obtained when its concentration was reduced.

[0019] As described above, by appropriately adding and controlling these elements, it is possible to obtain an excellent etched surface that maintains excellent smoothness even after etching and has less change in shape than before, leading to the invention of a stainless steel that is excellent in quality and suitable for etched products, such as the manufacture of spurs.

[0020] The present invention has been completed based on the findings obtained as described above. The austenitic stainless steel sheet for etching of the present invention has, by mass%, C: 0.010% or more and 0.10% or less, Si: 0.02% or more and 1.0% or less, Mn: 0.6% or more and 1.6% or less, Ni: 5.0% or more and 15.0% or less, Cr: 15.0% or more and 20.0% or less, Mo: 0.05% or more and 2.5% or less, W: 0.005% or more and 0.1% or less, %, Cu: 0.05% or more, 0.8% or less, N: 0.01% or more, 0.3% or less, B: 0.0001% or more, 0.0005% or less, and Sn: 0.002% or more, 0.02% or less, with the balance being Fe and unavoidable impurities, the ratio of the Cr concentration at the outermost surface to the Cr concentration in the base material being 0.90 or more, and the surface roughness (Ra) being 0.1 μm or less.

[0021] In the austenitic stainless steel sheet for etching according to the present invention, the preferred contents are Ti: 0.001% to 0.008%, Nb: 0.003% to 0.08%, and Co: 0.05% to 0.40%.

[0022] The present invention also provides a method for producing the above-mentioned austenitic stainless steel sheet for etching, which is characterized in that, in producing the above-mentioned austenitic stainless steel sheet for etching, the obtained slab is hot rolled, then cold rolled at a rolling ratio of 30% or more, and then heat treated at 800°C to 950°C. In the final rolling, the slab is cold rolled at a rolling ratio of 20% or more and 80% or less, and then a stress relief heat treatment is performed in a bright annealing furnace at 520°C to 750°C. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an etching process for obtaining spurs from the austenitic stainless steel sheet of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an etching process for obtaining spurs from a steel plate that does not satisfy the composition range of the present invention. [Diagram 3] FIG. 2 is a schematic diagram of a paper feed tester in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The reasons for limiting the chemical components of the austenitic stainless steel sheet for etching according to the present invention will be described below. In the following description, "%" indicates "mass %". C: 0.010 or more and 0.10% or less C is an austenite phase stabilizing element and is an important element for ensuring strength. For this reason, it is necessary to add at least 0.010%. However, if it is present in a large amount, depending on the heat treatment conditions, it is easy for it to precipitate in Cr carbide, causing sensitization and deteriorating corrosion resistance. For this reason, the upper limit is set to 0.10%. The preferred lower limit of the content is 0.015%, more preferably 0.020%, and the preferred upper limit is 0.06%, more preferably 0.04%.

[0025] Si: 0.02% or more and 1.0% or less Silicon is an important element with a deoxidizing effect, and therefore it is necessary to add at least 0.02% of silicon. However, it is also an element that promotes the precipitation of the σ phase, which deteriorates corrosion resistance. For this reason, the upper limit of the silicon content is set to 1.0%. The preferred lower limit of the silicon content is 0.30%, more preferably 0.40%, and the preferred upper limit is 0.8%, more preferably 0.7%.

[0026] Mn: 0.6% or more and 1.6% or less Mn is an element added as a deoxidizer, and because it stabilizes the austenite phase and increases the solubility of N, it suppresses the formation of carbonitrides and contributes to ensuring corrosion resistance. For this reason, it is necessary to include 0.6% or more. However, excessive addition forms MnS, which becomes the starting point of pitting corrosion and deteriorates corrosion resistance. In addition, coarse MnS makes the etched surface non-uniform and reduces smoothness. For this reason, the upper limit of the Mn content is set to 1.6%. The preferable lower limit of the content is 0.8%, more preferably 1.0%, and the preferable upper limit is 1.5%, more preferably 1.4%.

[0027] Ni: 5.0% or more and 15.0% or less Ni is an element that stabilizes the austenite phase, inhibits the precipitation of intermetallic compounds such as the σ phase, and is an important element that improves pitting corrosion resistance and general corrosion resistance. For this reason, Ni must be contained at 5.0% or more. However, if the Ni content exceeds 15.0%, the cost increases, so the Ni content is set to 5.0% or more and 15.0% or less. The preferred lower limit of the content is 5.5%, the more preferred lower limit is 6.0%, and the preferred upper limit is 14.0%, the more preferred upper limit is 13.0%.

[0028] Cr:15.0% or more and 20.0% or less Cr is an element that improves pitting corrosion resistance, crevice corrosion resistance, and intergranular corrosion resistance. If the content is less than 15.0%, corrosion resistance deteriorates, and if it exceeds 20.0%, the cost increases, so the content is limited to 15.0% or more and 20.0% or less. The preferred lower limit of the content is 16.0%, the more preferred lower limit is 17.0%, the preferred upper limit is 19.0%, and the more preferred upper limit is 18.0%.

[0029] Mo: 0.05% or more and 2.5% or less Mo is an element that improves corrosion resistance, and improves pitting corrosion resistance and crevice corrosion resistance. In addition, in the present invention, it is an important element that reduces the roughness of the sheet surface formed by annealing and pickling, and suppresses the formation of areas with low Cr concentration on the surface. This makes it possible to minimize the shape change of the etched surface. However, excessive Mo content greatly promotes the precipitation of σ phase, deteriorating corrosion resistance. For this reason, the Mo content is set to 0.05% or more and 2.5% or less. The preferred lower limit of the content is 0.06%, more preferably 0.07%, and the preferred upper limit is 2.4%, more preferably 2.3%.

[0030] W: 0.005% or more and 0.2% or less W, like Mo, is an element that improves pitting corrosion resistance and crevice corrosion resistance. In the present invention, W is an important element that reduces the roughness of the sheet surface formed by annealing and pickling, and suppresses the formation of areas with low Cr concentration on the surface. This makes it possible to minimize the shape change of the etched surface. However, excessive W content greatly promotes the precipitation of σ phase, deteriorating corrosion resistance. For this reason, the W content is set to 0.005% or more and 0.2% or less. The preferred lower limit is 0.008%, the more preferred lower limit is 0.01%, and the preferred upper limit is 0.19%, the more preferred upper limit is 0.18%.

[0031] Cu: 0.05% or more and 0.8% or less Cu is an austenite stabilizing element, and at 0.05% or more, it improves corrosion resistance, but at more than 0.8%, it deteriorates hot workability. Therefore, the Cu content is set to 0.05% or more and 0.8% or less. The preferred lower limit is 0.10%, more preferably 0.14%, and the preferred upper limit is 0.5%, more preferably 0.3%.

[0032] N: 0.01% or more and 0.3% or less N is an element that stabilizes the austenite phase, suppresses the precipitation of the σ phase, and is effective in improving strength. In addition, like Cr, Mo, and W, it is an element that greatly improves pitting corrosion resistance and crevice corrosion resistance. For this reason, it is necessary to add at least 0.01%. However, if the N content is excessive, a large amount of carbonitrides will precipitate, reducing corrosion resistance. Therefore, the upper limit of the N content is set to 0.3%. The preferred lower limit of the content is 0.03% or more, more preferably 0.05%, and the preferred upper limit is 0.20%, and more preferably 0.15%.

[0033] B: 0.0001% or more and 0.0005% or less B is an impurity element that may be inevitably mixed into steel from scrap, etc., and is also an element added in the present invention for the purpose of improving hot workability. It is essential in the steel of the present invention, which contains Sn, which reduces hot workability. For this purpose, it is necessary to add at least 0.0001% or more. It also affects the surface roughness after annealing and pickling, and when the B content exceeds 0.0005%, the surface roughness rapidly deteriorates. This is presumed to be because the scale generated during annealing becomes porous, making the surface rough after pickling. For this reason, the B content is set to 0.0001% or more and 0.0005% or less. The preferred lower limit of the content is 0.00012%, the more preferred lower limit is 0.00014%, the preferred upper limit is 0.00040%, and the more preferred upper limit is 0.00030%.

[0034] Sn: 0.002% or more and 0.02% or less In the present invention, Sn is an important element that reduces the roughness of the sheet surface formed by annealing and pickling, and suppresses the formation of a portion with a low Cr concentration on the surface. This makes it possible to minimize the shape change of the etched surface. In addition, the addition improves the corrosion resistance of the grain boundary due to the grain boundary segregation of Sn. These effects are small when the addition amount is less than 0.002%. Furthermore, when the addition amount exceeds 0.02% and the addition amount is large, hot workability is deteriorated, so the upper limit is set to 0.02% or less. The preferable lower limit is 0.0025%, the more preferable lower limit is 0.003%, the preferable upper limit is 0.014%, and the more preferable upper limit is 0.010%.

[0035] The ratio of the Cr concentration of the outermost surface to the Cr concentration of the base material is 0.90 or more. The reason why the ratio of the Cr concentration of the outermost surface to the Cr concentration of the base material is set to 0.90 or more will be explained. In the process of manufacturing a stainless steel sheet, after air annealing, a Cr-enriched oxide scale is formed, and a layer of a Cr-depleted layer with deteriorated corrosion resistance is formed directly below the oxide scale. The oxide scale is removed using nitric hydrofluoric acid in the pickling process, but the Cr-depleted layer directly below it remains. When the ratio of the Cr concentration of the outermost surface to the Cr concentration of the base material is 1.0, the etching ease of each crystal grain becomes equal, and a smooth etched surface can be obtained, so it is preferable that the ratio is close to 1.0. The ratio of the Cr concentration of the outermost surface to the Cr concentration of the base material is limited to 0.90 or more as a numerical value that does not affect the smoothness. A preferable range is 0.94 or more, and a more preferable range is 0.96 or more.

[0036] Ti: 0.001% or more and 0.008% or less Ti forms precipitates with C or N, improving intergranular corrosion resistance. It is also an effective element for preventing grain coarsening. However, excessive content of Ti causes excessive generation of Ti nitrides, which form clusters and cause surface defects. For this reason, the Ti content is set to 0.001% or more and 0.008% or less. The preferred lower limit of the content is 0.002%, more preferably 0.003%, and the preferred upper limit is 0.007%, more preferably 0.006%.

[0037] Nb: 0.003% or more and 0.08% or less Like Ti, Nb forms precipitates with C or N, improves intergranular corrosion resistance, and refines crystal grains, but as the content increases, it deteriorates hot workability. Therefore, the Nb content is set to 0.003% or more and 0.08% or less. The preferred lower limit is 0.004%, the more preferred lower limit is 0.006%, the preferred upper limit is 0.07%, and the more preferred upper limit is 0.06%.

[0038] Co: 0.05% or more and 0.40% or less Co, like C and N, is an element that stabilizes the austenite phase. C and N cannot be added in large amounts because they form carbonitrides with Ti and other elements, which can cause surface defects. However, Co is advantageous because it does not form carbonitrides. The effect of Co can be obtained by adding 0.05% or more. However, adding a large amount increases the cost of raw materials, so the amount is limited to 0.4% or less. The preferred lower limit is 0.075%, the more preferred lower limit is 0.10%, and the preferred upper limit is 0.35%, the more preferred upper limit is 0.30%.

[0039] Surface roughness (Ra) of the material surface and etched surface is 0.10μm or less Paper dust is generated due to the low degree of smoothness between the unetched material surface that comes into contact with the printed paper surface and the etched surface, and it is known that paper dust will not adhere even if generated if the surface roughness (Ra) is ≦0.10 μm or less. The surface roughness of the material surface is reduced by performing stress relief heat treatment in a bright annealing furnace, which suppresses the formation of oxide scale and results in a smooth surface. The etched surface is smoothed with less unevenness by improving the corrosion resistance of the grain boundaries by adding Sn, and by making the etching speed of the grain boundaries and the grain interior equal. The preferable upper limit of surface roughness (Ra) is 0.08 μm or less, and the more preferable upper limit is 0.06 μm or less.

[0040] Next, the reasons for limiting the conditions given in the manufacturing method of the present invention will be described. First, the rolling ratio of the first cold rolling is 30% or more because if the rolling ratio is less than 30%, sufficient strain that serves as a driving force for recrystallization is not introduced, and a mixed grain structure is formed in the subsequent heat treatment, causing the etched surface to become rough. Therefore, the rolling ratio is set to 30% or more. The preferable lower limit of the rolling ratio is 35%, and the more preferable lower limit is 40%.

[0041] The annealing according to the present invention can be performed by a conventional method. If necessary, a method of removing scale formed on the surface by pickling is used. In addition, a method of suppressing the formation of oxide scale by controlling the oxidation potential of the atmosphere is also suitable. For example, a method called bright annealing is performed in a nitrogen + hydrogen atmosphere with a hydrogen content of 70% or more, and a 100% hydrogen atmosphere is more preferable. In the first annealing after cold rolling, the annealing temperature must be 950°C or less to prevent roughening of the etched surface due to grain coarsening. The preferred upper limit of the annealing temperature is 940°C, and more preferably 930°C. In addition, the annealing temperature must be 800°C or more in order to recover ductility that enables the next cold rolling. The preferred lower limit is 810°C, and more preferably 820°C.

[0042] Next, in the final cold rolling, a rolling reduction of 20% or more is necessary to obtain finer crystal grains with uniform dislocation distribution within the crystal grains. Here, if cold rolling is performed at a rolling reduction of more than 80%, edge cracks are likely to occur during rolling, increasing the risk of breakage, so the upper limit of the rolling reduction is set to 80%. The preferred lower limit of the rolling reduction is 32%, more preferably 35%, and the preferred upper limit is 75%, more preferably 70%.

[0043] The heat treatment after the final rolling is a stress relief heat treatment, and is a heat treatment in a BA atmosphere. At temperatures below 520°C, residual stress inside the stainless steel sheet is not homogenized, causing warping during etching, so the lower limit temperature is set to 520°C. In addition, at annealing temperatures above 750°C, the etched surface is likely to become rough due to the growth of recrystallized crystal grains, so 750°C is set as the upper limit. The preferred lower limit of the stress relief heat treatment is 525°C, more preferably 530°C, and the preferred upper limit is 745°C, more preferably 740°C. EXAMPLES

[0044] Next, an example of the present invention that demonstrates the effects of the present invention will be described. A blank sheet made of alloys having the respective component compositions of alloys A to R and alloys S to X shown in Table 1 was prepared. In detail, raw materials such as scrap were put into an electric furnace and melted, and then decarburized by oxygen blowing in AOD (Argon Oxygen Decarburization) and / or VOD (Vacuum Oxygen Decarburization). After the refining process in AOD or VOD, the temperature was adjusted by ladle refining while stirring with Ar. Finally, a slab having a thickness of 200 mm was produced by continuous casting.

[0045] The manufactured slabs were heated at 1200 to 1270°C and hot-rolled to produce coils. The slabs were hot-rolled to a thickness of 3 mm, and then annealed and pickled to produce coils in which the 3 mm thickness was cold-rolled to a thickness of 0.8 mm (73.3% reduction). After that, in order to evaluate etching and other aspects, the slabs were annealed at 925°C, pickled to remove surface scale, and then cold-rolled again to 0.2 mm (75% reduction), and then subjected to SR treatment (stress relief heat treatment) at 550°C in a BA atmosphere for testing.

[0046] The obtained steel sheets were evaluated by the following methods. [Creating spur test pieces] A resist was applied to the obtained 0.2 mm thick steel plate, and a spur with an outer diameter of 25 mm, a tooth height of 1.25 mm, and 24 teeth arranged in a circle was produced by etching one side of the original plate on which the spur was drawn. The etching conditions were that ferric chloride solution (temperature: 60°C, liquid specific gravity: 1.45, oxidation-reduction potential: 680 mV) was sprayed onto the surface of the material at a pressure of 0.26 MPa for 34 minutes to produce the spur.

[0047] [Paper dust generation test] The 15 prepared spur test pieces were stacked, the tooth tips were aligned and tied. A paper feed test was then performed to compare the presence and amount of paper dust generated. A schematic diagram of the paper feed tester is shown in Figure 3. The printing paper 40 used for the test was fed to the spur test piece 14 side by two rollers, the main roller 32 and the pressure roller 30, and the process of discharging the paper by the spur test piece 14 fastened to the discharge roller 31 was simulated. The test was performed with a humidity of 80%, which affects the generation of paper dust. The paper feed speed was adjusted by the rotation speed of the two rollers and was set to 50 sheets / min. After feeding 1,000 sheets of plain paper, the weight of the paper dust generated was measured and evaluated. The paper dust was measured by sucking air around the test piece, capturing it with a filter, and measuring the filter with the paper dust as it was, and the weight of the filter before the test was calculated.

[0048] The evaluation was as follows: if the amount of paper dust generated was less than 500 mg, it was marked as ◎; if it was 500 mg or more but less than 700 mg, it was marked as ◯; if it was 700 mg or more but less than 1000 mg, it was marked as △; and if it was 1000 mg or more, it was marked as ×.

[0049] [Cr concentration analysis of surface and base material] The Cr concentration of the surface of the obtained 0.2 mm thick steel plate was analyzed using a Marcus type high frequency glow discharge emission surface analyzer (hereinafter GDS, manufactured by HORIBA, GD-Profiler2). The GDS is a device that performs element concentration profiling analysis in the depth direction by sputtering a sample with Ar plasma and making the sputtered atoms emit atomic light. Sputtering was performed from the surface to the plate thickness direction, and the value showing the lowest Cr concentration was taken as the Cr concentration of the surface, and the point where the ladle Cr% was reached from the surface was measured as the base material. The Cr concentration ratio of the surface to the base material was evaluated as ◎ if it was 0.96 or more, ○ if it was 0.94 or more but less than 0.96, △ if it was 0.90 or more but less than 0.94, and × if it was less than 0.90. The measurement conditions were excitation mode: pulse mode, sputtering method: Ar sputtering, sputtering pressure: 600 MPa, sputtering power: 8.75 W, pulse frequency: 100 Hz, and the analysis area was 4 mm in diameter.

[0050] [Measurement of surface roughness of material surfaces and etched surfaces] The surface roughness (Ra) was measured by cutting a 50 mm square test piece from the obtained 0.2 mm thick steel plate, applying resist to the entire back surface and a rectangular area of ​​25 mm x 50 mm in the center of the 50 mm x 50 mm front surface, and etching one side to prepare a surface roughness measurement test piece. The etching conditions were ferric chloride liquid (temperature: 60°C, liquid specific gravity: 1.45, oxidation-reduction potential: 680 mV) was sprayed on the surface of the material at a pressure of 0.26 MPa for 34 minutes to prepare a surface roughness measurement test piece. The prepared test piece was measured three times over a 200 μm length at a magnification of 1200 times using a 3D laser microscope (KEYENCE, VK-X3000), and the average value of the average arithmetic roughness for each was measured. The surface roughness of the material surface was measured along the direction parallel to the rolling direction. The surface roughness of the etched surface was measured near the 1 / 2 thickness part by fixing the surface roughness test piece vertically. The surface roughness (Ra) was evaluated as follows: 0.06 μm or less was rated as ⊚, 0.06 μm to 0.08 μm was rated as ◯, 0.08 μm to 0.10 μm was rated as △, and over 0.10 μm was rated as ×.

[0051] [Measurement of average crystal grain size] The average grain size is the grain size in the width direction of the plate on the cross section perpendicular to the rolling direction. The measurement position of the grain size is the center of the plate thickness 100μm into the plate thickness direction. The embedded sample was prepared by cutting a 25mm wide x 10mm long steel plate from the obtained 0.2mm thick steel plate and embedding it vertically. The etching conditions were 4mA load for 90 seconds in a 10% oxalic acid solution at 60℃. The grain size on five vertical lines was measured from a 2000x cross-sectional microstructure photograph using a digital microscope (KEYENCE, VHX-8000), and the average of 10 fields of view was calculated to obtain the average grain size. The evaluation was as follows: Average grain size of 3.0μm or less was ◎, 3.0μm to 3.5μm was ○, 3.5μm to 4.0μm was △, and over 4.0μm was ×.

[0052] [Hot workability evaluation] The coils were hot-rolled to a thickness of 3 mm, annealed and pickled, and then the number of sliver-shaped defects found on the coils was counted and evaluated. The number of defects per 10 m was converted into an ◎ for less than 2 defects, ◯ for 2 to 4 defects, △ for 4 to 6 defects, and × for 6 defects or more.

[0053] 〔comprehensive evaluation〕 As a comprehensive evaluation, examples including only ◎, ◯, and △ in each of the above evaluations were rated as passing, and examples including even one × were rated as failing. Note that parentheses are placed in the columns that do not satisfy the scope of the independent claims.

[0054] The evaluation results of each alloy are shown in Table 1. Alloys A to R are invention examples that satisfy the conditions of the present invention, while alloys S to X are comparative examples.

[0055] Alloys A to R shown in Table 1 contain sufficient Sn, Mo, and W, which prevents areas with low Cr concentration from forming on the surface, thereby reducing deformation of the spur shape and suppressing the generation of paper powder.

[0056] Since the S, T, and W alloys had low Mo, W, or Sn contents, low Cr portions were formed on the surface, which caused a large change in the shape of the spur teeth and generated a large amount of paper powder.

[0057] Since the U alloy had a high B content, the scale became porous during annealing, and the surface roughness (Ra) of the material surface decreased.

[0058] The V and X alloys had a low B content or a high Sn content, so many sliver-shaped defects occurred due to a decrease in hot workability.

[0059] Using alloy A shown in Table 1, spur test pieces were obtained from steel plates having a thickness of 0.2 mm under the manufacturing conditions shown in Table 2. Steel plates Nos. 1 to 4 are invention examples that satisfy the conditions of the present invention, while steel plates Nos. 5 to 9 are comparative examples.

[0060] The steel sheets No. 1 to 4 shown in Table 2 were sufficiently rolled to prevent the formation of a mixed grain structure, and were heat-treated at an appropriate temperature to give them a uniform structure. By performing stress relief heat treatment in a bright annealing furnace, the material surface was made smooth, which reduced the generation of paper powder.

[0061] Steel sheet No. 5 generated a large amount of paper powder because the surface roughness of the material after air annealing and pickling with nitric hydrofluoric acid became rough due to oxide scale.

[0062] The annealing temperature after cold rolling of steel sheet No. 6 was as high as 1000°C, which caused the crystal grains to become coarse, resulting in a rough etched surface and the generation of a large amount of paper powder.

[0063] The final rolling ratio of steel sheet No. 7 was low at 18%, resulting in a mixed grain structure and the roughening of the etched surface, which caused a large amount of paper powder to be generated.

[0064] The stress relief heat treatment temperature of steel plate No. 8 was as high as 800°C, and the etched surface was roughened by the mixed grain structure caused by partial recrystallization, resulting in the generation of a large amount of paper powder.

[0065] Because the initial cold-rolling reduction ratio of No. 9 steel sheet was low at 25%, sufficient strain to drive recrystallization was not introduced, resulting in a mixed grain structure in the subsequent annealing process, which resulted in the etched surface becoming rough and a large amount of paper powder being generated.

[0066] [Table 1]

[0067] [Table 2] [Explanation of symbols]

[0068] 10, 11: alloy plate, 12, 13: Cr-deficient layer, 14: spur, 20, 21: resist, 30: pressure roller, 31: paper discharge roller, 32: main roller, 40: printing paper

Claims

1. In mass percent, C: 0.010% or more, 0.10% or less, Si: 0.02% or more, 1.0% or less, Mn: 0.6% or more, 1.6% or less, Ni: 5.0% or more, 15.0% or less, Cr: 15.0% or more, 20.0% or less, Mo: 0.05% or more, 2.5% or less, W: 0.005% or more, 0.2% or less, Cu: 0.05% or more, 0.8% or less, N: 0.01% or more, 0.3% or less, B: 0.0001% or more, 0.0005% or less, Sn: 0.002% or more, 0.02% or less, and the balance consisting of Fe and unavoidable impurities, the ratio of the Cr concentration at the outermost surface to the Cr concentration in the base material is 0.90 or more, and the surface roughness (Ra) is 0.1 μm or less.

2. Ti: 0.001% or more, 0.008% or less, Nb: 0.003% or more, 0.08% or less, Co: 0.05% or more, 0.40% or less, 2. The austenitic stainless steel sheet for etching according to claim 1,

3. 3. A method for producing an austenitic stainless steel sheet for etching according to claim 1 or 2, comprising the steps of hot rolling the obtained slab, cold rolling it at a rolling reduction of 30% or more, heat treating it at 800°C to 950°C, and cold rolling it at a rolling reduction of 20% or more and 80% or less during final rolling, followed by heat treatment for stress relief in a bright annealing furnace at 520°C to 750°C.

Citation Information

Patent Citations

  • Stainless steel sheet for photoetching and production method therefor

    JP2003003244A

  • Stainless steel sheet for photoetching and its production method

    JP2005320586A

  • Stainless steel sheet for photoetching-processing and manufacturing method therefor

    JP2011012334A

  • Stainless steel plate and method for producing the same

    JP2020164905A

  • Stainless steel plate for photoetching and method for manufacturing the same

    JP4332670B2